Treatment of benign prostatic hyperplasia with 5-alpha-reductase inhibitor: morphological changes in patients who fail to respond. Issue 4 (April 1996) - Montironi, R; Valli, M; Fabris, G
Abstract : AIMS: To describe the prostatic adenectomy specimens of six patients with symptomatic benign prostatic hyperplasia (BPH) who failed to respond to long term treatment with a 5-alpha-reductase inhibitor, finasteride. METHODS: Histological sections from six cases of BPH who had been treated with finasteride were investigated. Five patients were prescribed 5 mg finasteride daily for six months and one patient 5 mg daily for 12 months. The patients underwent adenectomy as their urethral obstruction failed to resolve. Twenty cases of untreated BPH served as controls. RESULTS: In patients taking finasteride for six months the prostatic adenectomy specimens showed a reduction in the size of the prostate and an increase in the stroma:epithelial and stroma:lumen ratios compared with controls. The size of the ducts and acini was not as uniform as in the controls. In particular, some ducts and acini were still lined by a bistratified epithelium similar to that found in controls but lacked undulations at the epithelial border; other ducts/acini were atrophic. Some scattered clusters of small acini with a focally fragmented basal cell layer were observed in two of the five treated cases. One prostatic adenectomy specimen, from the patient treated for one year, showed extensive lobular atrophy and diffuse squamous and transitional cell metaplasia. At the periphery of the transition zone, there was a complex intra-acinar papillary-cribriform proliferation of clear cells without nuclear atypia, similar to clear cell papillary hyperplasia. The periurethral region showed stromal nodules in both patients and controls. CONCLUSIONS: Morphological evaluation of finasteride treated BPH showed changes in the lobules of the transition zone, but not in the periurethral stroma.